Missed opportunities: incomplete and inaccurate recording of paediatric early warning scores. Issue 12 (3rd July 2019) - Chapman, Susan M; Oulton, Kate; Peters, Mark John; Wray, Jo
Abstract : Background: Paediatric early warning scores (PEWS) are widely used as an adjunct to support staff in recognising deterioration in hospitalised children. Relatively little is known about how staff use these systems. Objective: To examine the completeness and accuracy of PEWS recording in hospitalised children in a tertiary specialist children's hospital. Design: This is a secondary analysis of retrospective, case-controlled study data. Case patients suffering from a critical deterioration event were matched with controls present on the same ward at the same time and matched for age. Data were extracted from the PEWS chart for the 48 hours before the critical deterioration event for case patients and the corresponding 48 hours period for the control. Observation sets were assessed for completeness and accuracy of PEWS scoring. Results: In total 297 case events in 224 patients were available for analysis. Overall 13 816 observations sets were performed, 8543 on cases and 5273 on controls. Only 4958 (35.9%) of observation sets contained a complete set of vital sign parameters and a concurrent PEWS. Errors were more prevalent in the observation sets of case patients versus controls (19.5% vs 14.1%). More errors resulted in the PEWS value being underscored rather than overscored for all observation sets (p<0.0001). 9.1% of inaccuracies for case patients were clinically significant, as the accurately calculated PEWS would have prompted a different escalation from the documented value. Conclusion: Failure to record complete and accurate PEWS may jeopardise recognition of children who are deteriorating. Technology may offer an effective solution.